Komunikasi dan Peranan Komisi Pemilihan Umum Kota Baubau dalam Meningkatkan Partisipasi Pemilih pada Pemilihan Umum Serentak Tahun 2024 - Haqqu, Erlina Sri Khadijatun; Maulana, Harry Fajar; Putra, Muh Rizal Ardiansah (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to analyze the performance of the Baubau City General Election Commission (KPU) in carrying out its duties and authority by Law Number 7 of 2017 and KPU Regulation Number 9 of 2022. The method used in this research is descriptive qualitative, supported by Lasswell's theory and Robert K. Merton's role theory. The research results show that the Baubau KPU has exceeded the national target in holding the 2024 Simultaneous Elections with a participation rate of 80.36%. In implementing voter outreach and education, the Baubau KPU ensures that communication runs clearly and effectively. The Baubau KPU carries out its role using various socialization methods such as face-to-face meetings in 43 sub-districts in collaboration with the Ad Hoc Agency and involving multiple parties such as the Regional Government, KesbangPol, Political Party Community Groups, NGOs, and Educational Institutions. Various superior programs run by KPU Baubau include seminars, workshops, discussions, and simulations that raise exciting topics related to elections held in multiple places, including KPU Goes to School, KPU Goes to Campus, KPU Goes to Islamic Boarding School, Election Carnival, Group Forum Discussion (FGD), Making a Video of 2024 Election Jingle Creation Exercises and Screening of the Film "Kejarlah Janji." The Baubau KPU also optimizes various mass media in the form of print and electronic media (online news) such as banners, brochures, pamphlets, posters, and social media on multiple platforms such as Instagram, Facebook, YouTube, and websites which aim to expand the dissemination of election-related information by upholding openness. And transparency of information to build public trust. In conclusion, the lack of human resources in managing social media and limitations in understanding technology and information has resulted in a need for updated information regarding elections on the YouTube platform and the Baubau KPU website. Keywords: Communication, Role of the Baubau City KPU, Simultaneous Elections in 2024